Video-opnames in die onderrig van liggaamlike opvoeding vir meisies van standerd 5-10 - Cruywagen, Mona (2014)
M.Ed. (Media Studies) === The task of the school is to use the various school subjects to assist pupils towards maturity. Each subject has a particular role to play in the education occurrence. Physical Education, which is a required subject, has its special role. A number of misconceptions about the educational values of Physical Education need to be cleared up. In addition, the questionnaire which served as a pilot study brought into focus some problems encountered in teaching this subject. In this study, the objectives of Physical Education form the basis of a demonstration of the position occupied by Physical Education in the education occurrence. It is imperative that all these objectives should be realised. There are, however, many teachers of Physical Education who experience difficulty in achieving these objectives on the cognitive, affective, movement, physical and social levels. Video is offered as a means to assist teachers in the attainment of the objectives of Physical Education. Using a detailed plan of a Physical Education lesson, demonstration is given at every phase of the lesson how a video programme can be integrated with the teaching. The unique characteristics of video, which differ from those of any other medium, make it possible for successful integration into every phase of a lesson. Using video, the teacher is placed in a better position to attain the objectives of Physical Education. It is important to realise that video cannot replace all the other educational media used by the Physical Education teacher and that it should not be considered the only solution to problem areas in the teaching of Physical Education.